Autogenous Dental Transplant - Clinical case report (Research, Society and Development, 2021)
Autogenous dental transplantation is characterized by the translocation of an element to another alveolar space. It is a procedure considered as a rehabilitation treatment, with a good prognosis mainly for young patients. Presenting as a great advantage the lower cost compared to the rehabilitation with implants and fixed prostheses, in addition to great acceptance by the patient for being his own tooth, without involving “nonself” materials. The objective of this work is to expose a case report on dental transplantation related to supernumerary teeth in the anterior region of the maxilla. In which it was carried out based on concepts of ethical principles and after signing the Informed Consent Form (ICF) by the person in charge. Melanoderma patient, 14 years old, presenting a supernumerary element in the region of element 11. After imaging studies, it was possible to notice the presence of element 11 impacted by palatine. The removal of the supernumerary and element 11 was performed, which was transplanted to its ideal alveolus, being maintained in position with the aid of semi-rigid containment. On the 35th postoperative day, the patient showed excellent recovery and healing of the periodontal tissues. Splinting was removed, with good stability of the unit, without mobility, absence of phlogistic signs or pulp changes to the vitality test. Radiographic examination showed good root adaptation, with no signs of resorption. However, the literature states that this follow-up must be carried out for up to 1 year, aiming to analyze pulp revascularization and the subsequent need for endodontics. To date, after 2 months of follow-up, the patient has no signs of pulp necrosis and is scheduled to start orthodontic treatment. Thus, it can be said that this is a valid and accessible rehabilitation treatment, and when properly indicated it brings good results.